Segmental Scleral Buckle: A Novel Strategy for Addressing Early Recurrent Inferior Retinal Detachment in Silicone Oil-Filled Eyes - Luca Ventre; Antonio Valastro; Erik Mus; Fabio Maradei; Giulia Pintore; Gabriella De Salvo (Life)
Recurrence of retinal detachment (RD) following pars plana vitrectomy (PPV) with silicone oil tamponade is a surgical challenge. This study proposes a novel approach utilizing segmental scleral buckle to manage early recurrences, especially in inferior quadrants. A retrospective case series of four patients with early recurrent inferior RD post-PPV with silicone oil tamponade was conducted. The segmental scleral buckle technique, with or without subretinal fluid drainage, was employed. Clinical and surgical data were collected, including visual outcomes and complications. No intraoperative or postoperative complications were observed during the 6-month follow-up period. Visual acuity remained stable, and retinal reattachment was achieved in 100% of cases after silicone oil removal. Segmental scleral buckle emerges as a promising technique for managing early recurrent inferior RD in silicone oil-filled eyes. The technique demonstrates favorable outcomes, including retinal reattachment and visual acuity stability, without significant complications. Further studies are warranted to validate its efficacy and establish standardized protocols.